Active Choice Framing and Intergenerational Education Benefits: Evidence from the Field - Benjamin L. Castleman; Francis X. Murphy; Richard Patterson; William L. Skimmyhorn (Institute of Labor Economics (IZA), 2019)
The Post-9/11 GI Bill allows service members to transfer generous education benefits to a dependent. We run a large-scale experiment to test whether active choice framing impacts US Army service members' decision to transfer benefits. Individuals who received email messages framing GI Bill use as an active choice between own use and transfer to a family member are more likely to pursue information about the benefit than individuals receiving outreach that does not frame the decision as an active choice. While we find no overall effect of framing on transfer, active choice increases transfer among service members with graduate degrees.
Keywords: D15; D91; H52; I24; 330; active choice; GI Bill; randomized controlled trial